Identifying and Prioritizing Research Gaps in Studies related to Total Quality Management on Competitive Advantage in Malaysian Hotel Industries - Sin, Kit Yeng; Muhammad Shahar, Bin Jusoh (Human Resource Management Academic Research Society, 2019)
Determining research gaps is a cardinal goal in literature review. While it has been diffusely conceded that literature reviews should determine research gaps, no methodological orientation is available on how to pinpoint research gaps amidst review of literature or to assure rigor and replicability. Hence, this study addresses this gap and puts forward a simple prototype that should assist scholars in this endeavour without suppressing creativity. Based on the study outcomes, a technique has been generated to identify research gaps, so as to enable scholars to conduct a more rigorous, effective, and efficient literature reviews henceforth.